EFFECT OF THE RATIO OF BROWN RICE FLOUR AND MUNG BEAN FLOUR ON THE PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF SEMPRONG CAKE - Sahid, Emif Rezqia; Lestari, Oke Anandika; Hartanti, Lucky (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2025)
Brown rice flour and mung bean flour are food ingredients that are rarely used but have potential as ingredients in making semprong cakes. The purpose of this study is to obtain the right ratio of brown rice flour and mung bean flour to produce the best semprong cake formulation based on physicochemical and sensory characteristics. The research was conducted using the Group Random Design (RAK) method with one factor, namely the ratio of brown rice flour and mung bean flour. The observed parameters include moisture content, protein content, ash content, color, and sensory analysis. The data obtained was analyzed using ANOVA and if it was effective, further tests were carried out using the honest real difference test (BNJ) with a level of 5%. Based on the results of the semprong research, the best formulation is semprong with a ratio of 60% brown rice flour and 40% mung bean flour with a moisture content of 3.30%, protein content of 16.80%, ash content of 1.56%, color L* 23.26, color a* 6.62, color b* 7.54, as well as sensory scores for color 4 (dark chocolate), aroma 3 (typical of brown rice), texture 4 (crispier), and taste 4 (more savory).